ANALISIS KADAR COD PADA LIMBAH AIR LINDI MENGGUNAKAN SISTEM MEMBRANE BIO REACTOR (MBR) DI TPA SUPIT URANG KOTA MALANG - Risky Amalia; I Gusti Made Sanjaya (Unesa Journal of Chemistry, 2026)
Leachate is a highly polluted liquid generated from landfill waste and requires proper treatment before being discharged into the environment. This study aims to analyze the changes in Chemical Oxygen Demand (COD) levels in leachate wastewater before and after treatment using a Membrane Bioreactor (MBR) system at Supit Urang Landfill, Malang City. The research was conducted at the laboratory of the Waste Management Unit (UPT) of Malang City. Four sampling points were analyzed, namely Measuring Device A (MDA), inlet pump, outlet pump, and Measuring Device B (MDB). COD analysis was carried out using a thermoreactor and colorimeter and was performed in duplo for the same sample. The results showed a significant decrease in COD levels from 3460 mg/L at MDA to 96 mg/L at MDB after treatment through the MBR system with reduction efficiency of approximately 97.2%. This reduction indicates that the MBR system effectively removes organic pollutants in leachate wastewater. The final COD value meets the environmental quality standard set by the Indonesian regulation (maximum 300 mg/L). Therefore, the MBR system can be considered an effective technology for leachate wastewater treatment.